2018
DOI: 10.5614/j.math.fund.sci.2018.50.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Tree Community Structure and Composition of a One-Hectare Permanent Plot in the Montane Zone of Mount Kerinci, Kerinci Seblat National Park, Jambi

Abstract: Information on tree community structure and composition is needed in forest management and restoration. These data can be obtained using a permanent plot for studying forest dynamics, including species-specific characteristics. These characteristics are useful in the identification of native species for commercial and restoration purposes. This study aimed to describe the tree community structure and composition of a one-hectare permanent plot in the montane zone of Mount Kerinci. Data collection was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 19 publications
(35 reference statements)
3
7
2
Order By: Relevance
“…Tree Diversity Species richness of tree in two sampling sites was not different. This result is similar to Sulistyawati et al (2018) but lower Yamada (1975) . Lower species richness in two sampling site could be affected by altitude difference, size of the plot and past threats in Ketambe sampling plot.…”
Section: Summary Of the Studysupporting
confidence: 85%
See 4 more Smart Citations
“…Tree Diversity Species richness of tree in two sampling sites was not different. This result is similar to Sulistyawati et al (2018) but lower Yamada (1975) . Lower species richness in two sampling site could be affected by altitude difference, size of the plot and past threats in Ketambe sampling plot.…”
Section: Summary Of the Studysupporting
confidence: 85%
“…Burangrang, Purwaningsih et al (2017) in Mt. Wilis, and absent in other previous studies in mountain area (Cahyanto et al, 2020;Sulistyawati et al, 2018;Yamada, 1975) Most of the families can be found on both sites. 13 families can be found on both sites.…”
Section: Species Composition and Succession Statusmentioning
confidence: 48%
See 3 more Smart Citations